2018
DOI: 10.1155/2018/4041873
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Orally Administered Atractylodes macrocephala Koidz Water Extract on Macrophage and T Cell Inflammatory Response in Mice

Abstract: The rhizome of Atractylodes macrocephala Koidz (AM) is a constituent of various Qi booster compound prescriptions. We evaluated inflammatory responses in macrophages and T cells isolated from mice following oral administration of AM water extract (AME). Peritoneal exudate cells were isolated from thioglycollate-injected mice and alterations in scavenger receptors were examined. Peritoneal macrophages were stimulated with lipopolysaccharide (LPS). Serum cytokine responses to intraperitoneal LPS injection were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…During inflammation, bone marrow-derived monocytes are recruited to the site and differentiate into macrophages [ 16 ]. Macrophages eliminate pathogens and antigens through phagocytosis and induce inflammatory responses by producing cytokines and enzymes such as TNFα, IL6, inducible nitric oxide synthase (iNOS), and cyclooxygenase-2 (COX2) [ 17 ]. Inflammatory cytokines are generally classified as pro-inflammatory (IL1, IL4, IL6, IL12, IL15, IL17, IL23, TNFα, and IFNγ) or anti-inflammatory (IL10 and TGFβ) [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…During inflammation, bone marrow-derived monocytes are recruited to the site and differentiate into macrophages [ 16 ]. Macrophages eliminate pathogens and antigens through phagocytosis and induce inflammatory responses by producing cytokines and enzymes such as TNFα, IL6, inducible nitric oxide synthase (iNOS), and cyclooxygenase-2 (COX2) [ 17 ]. Inflammatory cytokines are generally classified as pro-inflammatory (IL1, IL4, IL6, IL12, IL15, IL17, IL23, TNFα, and IFNγ) or anti-inflammatory (IL10 and TGFβ) [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Injection of TG into the peritoneal cavity is a traditional method of inducing inflammation in the peritoneal cavity and promoting the migration of inflammatory cells, including T cells [ 36 ]. In the abdominal cavity, there are immune cells, such as macrophages and lymphocytes, and the number of these cells increases in response to various stimuli [ 37 , 38 ]. Compared to the LPS-induced peritonitis model in mice, we obtained more lavaged immune cells, such as macrophages and lymphocytes, in the TG-treated model (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…For example, An animal study reported that Atractylodes macrocephala Koidz. water extract administered orally could increase the CD4 + T cell population in the spleen of mice stimulated with lipopolysaccharide ( Kwak et al, 2018 ). According to an vitro study, polysaccharides derived from Atractylodes macrocephala Koidz.…”
Section: Discussionmentioning
confidence: 99%